Somatic embryogenesis from mature caryopsis culture under abiotic stress and optimization of Agrobacterium-mediated transient GUS gene expression in embryogenic callus of rice (Oryza sativa L.) - Vikrant, Vikrant; Maragathamani, R; Khurana, Paramjit (Journal of Phytology, 2012)
Induction and development of embryogenic callus from mature caryopsis culture of rice (Oryza sativa cv. ADT41) was performed by placing sterilized seeds on MS medium supplemented with 2,4-dichlorophenoxyacetic acid or 2,4-D (2.5, 5.0 and 10 mg/l). Morphogenesis in terms of somatic embryogenesis was recorded and 53% embryogenic callus formed by caryopsis culture indicates high chance of regenerating plants eventually. Furthermore, for water stress treatments, sterilized caryopses were cultured on semisolid MS medium supplemented with (5.0mg/l) of 2, 4-D and various concentrations of mannitol (2.5M, 5M and 10M) were added. Present study indicates that potentials of tissues for callus induction and embryo differentiation gradually decline if the level of mannitol is being increased in the nutrient media. Significantly, at high level of mannitol (5M), direct somatic embryo differentiation from the epicotyl tissues was also evident along with embryogenic callus formation at the basal region of the seedling. Similarly for salt stress treatments, MS medium was supplemented with various concentrations of NaCl (50 mM, 100 mM and 250 mM) along with 2, 4-D (5.0 mg/l). Results obtained on salt–stress treatments indicate that cultured rice cells may respond variously depending on the concentration of salt-stress present in the culture medium. Also, transformation experiments were conducted to optimize the transient GUS gene expression in mature caryopsis derived embryogenic callus by employing the various strains of Agrobacterium tumefaciens carrying the same plasmids or others. Calli were co-cultivated with Agrobacterium strains GV2260 (p35SGUSINT), LBA4404 (p35SGUSINT) and LBA4404 (pCAMBIA 3301) in the presence of acetosyringone (200 μM). Transformation events were best recorded in calli treated with Agrobacterium strain LBA4404 harbouring the plasmid p35SGUSINT, as evidenced by maximum frequency (29%) of transient GUS gene expression on histochemical assay and it was followed by strain GV2260 (p35SGUSINT), however, Agrobacterium strain LBA4404 (pCAMBIA3301) could be proved the least effective in terms of frequency of transient transformation and expression of GUS reporter gene in target tissues.